Novel on-resistance based methodology for MOSFET electrical characterization. (June 2020) - Karatsori, T.A.; Bennamane, K.; Ghibaudo, G.
Abstract: A new methodology for MOSFET characterization making use of the on-resistance characteristics Ron (Vg, Vd ) = Vd /Id (Vg, Vd ) and associated derivatives dRon /dVg and dRon /dVd is proposed. This approach enables to eliminate the influence of source-drain series resistance Rsd not only in linear region but also in non-linear region of MOSFET operation. Therefore, it allows for intrinsic MOSFET parameter extraction free from source and drain series resistance.